Risk & prevention: building characteristics and occupancy implications on Indoor Air Quality (IAQ) in selected day care nursery and primary school in Pahang - Mohd. Aris, Mohd Shukri; Yunus, Kamaruzzaman; Abu Samah, Mohd Armi (2016)
Introduction: The effects of children’s exposure on high concentration of airborne pollutants at day care nursery and schools often associated with increased rate of absenteeism and hospital admission, low productivities and learning performances, and development of respiratory problems. Instead of concentrating on outdoor-indoor air quality relationships, recent studies have found that the presence of occupants in the nursery room and classroom seems to give major effect towards the elevation of concentration of airborne pollutants in indoors. To evaluate and further understand on the significance of occupancy factor on IAQ, this study was designed to investigate its relationships and degree of exposure of airborne pollutants towards these leaders of tomorrow. Objectives: This study aims to determine and compare the level of selected physical (particulate matter (PM)) and chemical (carbon dioxide (CO2) and temperature) IAQ parameters and biological contaminants via colony forming unit (CFUm-3) for bacteria and fungi inside the selected classrooms during occupied and non-occupied period. The second objective is to describe the possible sources of airborne pollutants inside the nursery and classrooms at the selected buildings based on referral location as urban, residential and rural area in Pahang. Methods: Physical and chemical IAQ assessments were done using instruments known as DustMate Environmental Dust Detector and VelociCalc® Multi-Function Ventilation Meter 9565. The data were recorded every 30 min for 8 hours during schooldays and weekend at the selected sampling point in the buildings. For microbial sampling, Surface Air System Indoor Air Quality (SAS IAQ) was used to capture the bacteria and fungi. The data obtained were compared with the established standard reference known as the Industrial Code of Practice on Indoor Air Quality (2010) constructed by the Department of Occupational Safety and Health (DOSH), Malaysia. Outcomes & recommendation: This study found that some of the IAQ parameters in the selected nursery and classrooms were exceeding the established standards during occupied period in schooldays compared to non-occupied period during weekend. Findings of this study provide the insights for future research including the site selection of school, arrangement of the classrooms and numbers of students per class. In addition, health screening especially related to respiratory system also can be suggested to the children for early detection and prevention from any adverse effects due to IAQ. These possible prevention approaches will introduced the relevant guidelines and procedures in building design and operation for newly setup of nursery and primary school which can be implemented anywhere particularly for Perak state.